Pengaruh PENGARUH CITRA DAN REPUTASI INSTITUSI TERHADAP PERSEPSI SISWA SLTA UNTUK KULIAH DI ISI PADANGPANJANG - Syafran Syafran; Harissman Harissman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
ABSTRACT This research aims to test the effect of brand image and campus reputation to the perception of senior high school students’ to study at Institut Seni Indonesia Padang Panjang by surveying samples of 487 of twelfth class students of senior high school, senior vocational school and religious or aliyah school in 15 school institutions that located in 6 regencies/cities of West Sumatera Province. Result from coefficient regression (t test) showed that independent variable of brand image was positively significant take effect to the perception of senior high school level students’ to study at Institut Seni Indonesia Padang Panjang then, the independent variable of reputation was positively significant take effect to the dependent variable of perception. Moreover, when it tested by coefficient determination that tested all the independent variables to the dependent variable it showed that there were R-Square value with 0,546 which meant that there were 54,6 % proportion of effect of all independent variables to the dependent variable. Keywords: effect, brand image, reputation, perception, study at ISI Padangpanjang